Nationalism as a Question for Theology – A Few Remarks on a Dividing Issue - Attila János BORSI (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
Nationalism remains to be one of the most compelling issues of communities. It raises questions not only for humanities but for theology as well. Thus, we approach it from the perspective of Reformed theology with the aim of trying to find such a point of reference by which Christian thinking is able to pro-vide orientation in understanding this problem. The article first visits such basic definitions as state, nation, or people and attempts to define them. By providing inputs to this clarification from a theological point of view, the article investigates how the Christian doctrine of providence with its emphasis on the vertical dimension of human life can help us to avoid the absolutization of the notion of nation. One of the main points of the text is to differentiate between national existence and nationalism. Nationalism cannot be justified, such as decontextualized national existence since one of the main consequences would be a misunderstood concept of progress. A correctly articulated national existence always brings to the fore the concern for sovereignty. The article argues that a nation’s sovereignty from the Christian point of view can be neither detached from the sovereignty of God nor expressed without taking it seriously. Since proper sovereignty is only to be practised not against but for something, it always points to-wards God’s sovereignty.